Promoting Harmony in Communication: The Role of Inclusive Language in Enhancing Equility and Equity in Digital Platforms - Bima Kurniawan (Universitas Muhammadiyah Tangerang, 2025)
This research aims to enrich academic discourse on inclusive language by exploring its role in creating harmony in digital communication through the use of shared, non-offensive and accommodating language. This research uses a descriptive qualitative method with a case study approach. Triangulation was carried out to identify consistency of data from various sources, thereby increasing the validity of the findings. Data collection methods include interviews, focus group discussions (FGD) with 10 colleagues who have visual impairments, observation, and documentation. As researchers with visual impairments, researchers have a significant role in assessing the accessibility of social media, news platforms, and public service media for users with screen readers. The research results show that common language has been implemented well in various digital communication media. Recommendations for significant improvements were emphasized, especially in the use of accommodating language for accessibility features in news media. It is hoped that the practical implications of this research can provide recommendations to the government and policy makers in managing social media, news media and public service media, to create policies and technical guidelines for implementing a common, accommodating and non-offensive language. These findings will benefit not only individuals with visual impairments, but also people with other disabilities as well as non-disabled individuals, by ensuring inclusive communication for all.